Managerial ties, strategic initiatives, and firm performance in Central Asia and the Caucasus - Ismail, K.; Ford, D.; Wu, Q.; Peng, Mike (Springer New York LLC, 2013)
Managerial ties are an area commanding managers' attention in emerging economies. However, no previous study has drawn on cross-country data to address a crucial question: Are more developed market-supporting institutions associated with less use of managerial ties in emerging economies? Further, to strive for better performance, firms also need to develop market-based strategic initiatives. How do these initiatives impact performance? What role do managerial ties play in the relationship? Addressing these questions, this article extends research on managerial ties in emerging economies to an underexplored region-Central Asia and the Caucasus.